Modern level of scientific, innovative and patent activities in Ukraine - Fesenko, O.M.; Korskanov, V.V.; Budnyk, O.P.; Pogoretskii, P.P. (Наука та інновації, 2020)
Introduction. The development of patent and innovation is impossible without a strong scientific base. That is why the R&D potential of the state is one of the main factors that reflect the level of both economic and technical level of its development. Unfortunately, the level of patent innovation in Ukraine is low, despite the strong R&D potential. Problem statement. The efficiency of innovations, trends in nanotechnology patenting, and the level of nanotechnology development in Ukraine are mainly determined by the qualifications of Ukrainian researchers. Therefore, preserving the R&D potential of Ukraine and preventing its outflow abroad are among the most pressing problems today. Purpose. To determine the role of R&D in the economy of Ukraine and the world, the level of publications of Ukrainian authors, the effectiveness, patent circulation, and prospects of innovations in Ukraine. To characterize the world market of nanotechnologies and the level of development of nanotechnologies in Ukraine and to provide a forecast of innovative development in Ukraine and the world. Materials and Methods. Statistical data of R&D potential of Ukraine, number of research works in Ukraine, materials on the quantitative and qualitative level of scholarly research publications of Ukrainian authors, patent circulation, the efficiency of innovations in Ukraine for the period 2010—2017, for forecasting of innovative development in Ukraine and the world on the coming decades. Results. The R&D potential of Ukraine, the current level of nanotechnology, innovation, and trends in their further development have been evaluated. The innovative development in Ukraine and the world until 2030 has been forecasted. Conclusions. Ukraine has a strong R&D potential, but the level of patent and innovation activity in Ukraine is low. Against the background of the integration of Ukrainian researchers into the world community, there is a significant increase in the number of joint scholarly research publications of Ukrainian researchers with foreign colleagues. Вступ. Розвиток патентної та інноваційної діяльності неможливий без потужної наукової бази. Саме тому науковий потенціал держави є одним з основних факторів, що відображає рівень як економічного, так і технічного рівня її розвитку. На жаль, в Україні рівень патентно-інноваційної діяльності є низьким, незважаючи на потужний науковий потенціал. Проблематика. Ефективність інновацій, тенденції патентування нанотехнологій та рівень розвитку нанотехнологій в Україні головним чином визначаються кваліфікацією українських науковців. Тому проблеми збереження наукового потеціалу України та запобігання його відтоку за кордон є одними з найактуальніших на сьогодні. Мета. Визначити роль наукових досліджень в економіці України та світу, рівень публікацій українських авторів, ефективність, патентний обіг та перспективи інновацій в Україні. Охарактеризувати світовий ринок нанотехнологій та рівень розвитку нанотехнологій в Україні та надати прогноз інноваційного розвитку в державі та світі. Матеріали і методи. Використано статистичні дані наукового потенціалу України, кількості науково-дослідних робіт в Україні, матеріали щодо кількісного та якісного рівня наукових публікацій український авторів, патентного обігу, ефективності інновацій в Україні за період 2010—2017 рр. для прогнозування інноваційного розвитку в Україні та світі на найближчі десятиліття. Результати. Зроблено оцінку наукового потенціалу України, сьогоднішнього рівня нанотехнологій, інновацій та тенденцій їхнього подальшого розвитку. Cформовано прогноз інноваційного розвитку в Україні та світі до 2030 року. Висновки. Україна має потужний науковий потенціал, але рівень патентної та інноваційної активності в Україні низький. На фоні інтеграції українських науковців у світову спільноту спостерігається значне збільшення кількості спільних наукових публікацій українських науковців із закордонними колегами.